Implementation of the global equipment efficiency indicator - OEE in large drills in a mining company (Research, Society and Development, 2022)
The theme presented in this article was the implementation of the global efficiency indicator, also called OEE, in two large rigs, which are in operation at a company in the mining sector. The objective, therefore, was to evaluate this process of implantation of the OEE in these equipments, making the respective calculations for its application. For this, the methodology used was data collection in the field to carry out such calculations, carried out with the support of bibliographical research, which brought theoretical foundation on the verified subject. As a result, from the theoretical studies mentioned on the subject, data were collected in the mining area, such as the characterization of the rigs and their respective values of maintenance hours and drill holes, to verify their availability, performance and quality. From this, the OEE was calculated in both equipments. The percentage of the overall efficiency of rig 1 was considered unacceptable, while that of rig 2 was considered good, but both results are far from the ideal value. In conclusion, it can be seen that interventions are needed in order to improve the equipment in the availability indicators, but mainly in performance, since low values of the same were reflected in the final value of the OEE, which was also low.